To solve the equation \(-3x - 6 + \frac{1}{8} = -\frac{1}{4}\), we first isolate \(x\).
-
Start by combining constants on the left side: \[ -3x - 6 + \frac{1}{8} = -\frac{1}{4} \]
-
To combine \(-6\) and \(\frac{1}{8}\), we convert \(-6\) to a fraction: \[ -6 = -\frac{48}{8} \] So, \[ -3x - \frac{48}{8} + \frac{1}{8} = -\frac{1}{4} \]
-
Combine the fractions on the left side: \[ -3x - \frac{48}{8} + \frac{1}{8} = -3x - \frac{47}{8} \]
-
Now we have: \[ -3x - \frac{47}{8} = -\frac{1}{4} \]
-
Convert \(-\frac{1}{4}\) to a fraction with a denominator of 8: \[ -\frac{1}{4} = -\frac{2}{8} \]
-
Substitute this back into the equation: \[ -3x - \frac{47}{8} = -\frac{2}{8} \]
-
Add \(\frac{47}{8}\) to both sides: \[ -3x = -\frac{2}{8} + \frac{47}{8} \] \[ -3x = \frac{45}{8} \]
-
Divide both sides by -3: \[ x = \frac{45}{8} \times -\frac{1}{3} = -\frac{45}{24} \]
-
Simplify \(-\frac{45}{24}\): \[ x = -\frac{15}{8} \]
Thus, the value of \(p\) that makes the equation true is: \[ p = -\frac{15}{8} \]